A review on the values of Islamic garden in response to a garden design in Malaysia - Md Jani, Haza Hanurhaza; Harun, Nor Zalina; Mansor, Mazlina; Zen, Ismawi (Springer, 2018)
This chapter aims to investigate the physical characteristics of the Islamic garden and discover the values which can be adapted to a garden design in Malaysia. The chapter reviews several significant aspects for developing an understanding of the Islamic garden and its characteristics. There are two methods embedded in the chapter, namely, document analysis and semi-structured interviews. The outcome of the chapter highlights the importance of strengthening an understanding of the Islamic garden as a key to protecting and perpetuating the legacy of the Muslim civilisation.